Molecular Prevalence of Ent amoeba histolytica and Ent amoeba dispar Infection among Aboriginal Communities in the Southern Region of Perak, Malaysia - Saidin, Syazwan; Abu Bakar, Adibah; Bun Poh, Remmy Keong; Raja Khairuddin, Raja Farhana; Md Zain, Badrul Munir (IIUM Medical Journal Malaysia, 2022)
INTRODUCTION: In Malaysia, there are little up-to-date data on the prevalence of Ent amoeba spp. and most of the previous studies were carried out using the conventional insensitive method of stool microscopic examinations. MATERIALS AND METHODS: A cross-sectional study was conducted from September 2018 to Mac 2019 in the three villages of Orang Asli communities at Slim River, Perak using the molecular assay. Risk factors associated with Ent amoeba spp. infection was assessed by analysing questionnaire responses obtained from the study participants. RESULTS: From the 55 stool samples collected, molecular prevalence revealed 7.3% and 9.1% E. histolytica and E. dispar infection respectively. Infection was due to indiscriminate defecation and not washing hands after playing with soil or gardening, as well as associated with gastrointestinal symptoms. CONCLUSION: This study showed that there is still an ongoing transmission of Ent amoeba spp. among the studied population, thus warrants the implementation of specific prevention and control strategies of this infection in Malaysia.